Interrupted breeding in a songbird migrant triggers development of nocturnal locomotor activity - Mukhin, Andrey (Sci Rep, 2018)
Long-distance avian migrants, e.g. Eurasian reed warblers (Acrocephalus scirpaceus), can precisely schedule events of their annual cycle. However, the proximate mechanisms controlling annual cycle and their interplay with environmental factors are poorly understood. We artificially interrupted breeding in reed warblers by bringing them into captivity and recording birds’ locomotor activity for 5–7 days. Over this time, most of the captive birds gradually developed nocturnal locomotor activity not observed in breeding birds. When the birds were later released and radio-tracked, the individuals with highly developed caged activity performed nocturnal flights. We also found that reed warblers kept indoors without access to local cues developed a higher level of nocturnal activity compared to the birds kept outdoors with an access to the familiar environment. Also, birds translocated from a distant site (21 km) had a higher motivation to fly at night-time after release compared to the birds captured within 1 km of a study site. Our study suggests that an interrupted breeding triggers development of nocturnal locomotor activity in cages, and the level of activity is correlated with motivation to perform nocturnal flights in the wild, which can be restrained by familiar environment.